KESULITAN MEMBACA PEMAHAMAN SISWA KELAS IV SDN 112 PEKANBARU - Selviani Rahmawati; Febrina Dafit (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Education is important to meet students needs. This is in line with Article 5 of Law Number 20 of 2003 concerning the National Education System which states that everyone has the right to obtain a decent education. Early basic education is very important in the development of students' personalities. Elementary school is the initial stage of basic education and functions as a foundation for students linguistic development. Reading, writing, listening and speaking are part of the language skills that must be mastered. Reading is a key element of language ability. Reading is very important for gathering knowledge and gaining understanding. Reading comprehension is an activity carried out seriously by the reader in order to obtain various information, messages and meanings contained in a text. The purpose of this research is to describe students reading comprehension difficulties, factors that influence students reading comprehension difficulties, solutions to students reading comprehension difficulties. The method used is qualitative to analyze data with a descriptive case study approach, with data collection techniques of tests, observations, interviews with teachers and class IV students.